Review of Evidence and Perspectives of Flavonoids on Metabolic Syndrome and Neurodegenerative Disease - Zilli, Aline M. Hilzendeger; Zilli, Eduardo M. (Protein and Peptide Letters, 2021)
Flavonoids are commonly found in fruits, vegetables, and plant-derived foods and may promote various health benefits when included in the diet. The biological activity of flavonoids is normally associated to their potent antioxidant and anti-inflammatory effects, since oxidative stress is associated to conditions such as diabetes, obesity, cardiovascular and neurodegenerative diseases. Additionally, flavonoids may be related to metabolic diseases through their effects on inflammatory mediators and pathways, barrier integrity and gut microbiota composition. The extensive metabolism undergone by flavonoids in humans and the individual differences in their bioavailability to target organs hinder the interpretation of results from cell and animal models. Prospective human studies therefore provide an important perspective. In the field of neurodegenerative disease, carefully designed cohort studies have uncovered important associations between flavonoid intake and reduction in dementia risk, especially regarding specific flavonols, but also anthocyanins. Alternative mechanisms of action, such as changes in the gut microbiota or modulation of the production of toxic proteins, such as amyloid and tau, likely account for an important component of their positive effects, and their elucidation may lead to public health benefits of large magnitude.
Keywords: gut microbiota